Picture Book Development as a Response to the Early Literacy Crisis and Efforts to Increase Children's Interest in Reading - Oktavianti, Annisa Ika; Nur, Nuzulul Alifin (Jurnal Pengabdian Masyarakat, 2024)
Purpose: The objective of this research is to enhance children's enthusiasm for reading and improve their literacy abilities by introducing innovative forms of children's literacy media, such as picture books. The researchers created a visual publication specifically designed for sixth-grade students at SD Negeri 2 Pandeyan. The purpose of this book is to inspire and engage youngsters, ultimately fostering a greater enthusiasm for reading and addressing the issue of early literacy challenges. Method: The research employed a qualitative methodology. The activity is structured into three distinct stages: (1) preparation, involving observations and interviews; (2) implementation, which includes creating picture books, promoting children's literature and picture books, and engaging in group reading sessions; and (3) evaluation, which entails self-reflection and assessing the performance of the service program. Practical Applications: Seventeen grade VI children at SD Negeri 2 Pandeyan strongly valued picture books as a form of non-academic reading. Schools should maintain children's literature, particularly picture books, by offering non-academic reading resources to foster a greater interest in reading. Conclusion: Therefore, the specific early literacy crisis in Pandeyan Village can be mitigated. It is crucial to foster children's interest in reading at a young age in order to cultivate their literacy skills, which will then be sustained throughout their adult lives.